STRATEGI PENGUATAN AGROINDUSTRI SAGU KABUPATEN KEPULAUAN MERANTI UNTUK MENINGKATKAN DAYA SAING PRODUK LOKAL - Yuri Marisa; Diva Tri Ramadani; Renata Deliana; Muhammad Bintang Anugrah; Eka Armas Pailis (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study was motivated by the enormous potential of sago in the Meranti Islands Regency as the area with the highest acreage and productivity in Riau Province, but which has not yet provided optimal added value to the community's economy due to limitations in technology, markets, and MSME capacity. The study aims to formulate strategies for strengthening the sago agroindustry through a SWOT analysis summarized in IFAS and EFAS matrices to assess its strategic position and development alternatives. The results show that sago productivity has increased, but downstreaming and product quality are not yet optimal. The strategic position is in the Hold and Maintain category, indicating sufficient internal strength but facing external pressures such as competition and limited infrastructure. The strengthening strategy focuses on technological modernization, SME empowerment, product development, digital market expansion, quality certification, and integrated upstream-downstream partnerships to enhance competitiveness and sustainable community welfare.